Duration of the second stage of labour and risk of subsequent spontaneous preterm birth. (29th January 2022) - Kleinstern, Geffen; Zigron, Roy; Porat, Shay; Rosenbloom, Joshua I.; Rottenstreich, Misgav; Sompolinsky, Yishay; Rottenstreich, Amihai
Abstract: Objectives: To determine the risk of spontaneous preterm birth (sPTB) associated with the length of second stage of labour in the first term delivery. Design: Retrospective cohort study. Setting: University hospital. Population: Women with first two consecutive singleton births and the first birth at term. Those who did not reach the second stage of labour in the first delivery were excluded. Methods: Charts from 2007 to 2019 were reviewed. Main outcome measures: Rate of sPTB (<37 weeks of gestation) in the second delivery. Results: Of 13 958 women who met study inclusion criteria, 1464 (10.5%) parturients had a prolonged second stage (≥180 min) in their first term delivery. The rate of sPTB in the second delivery was similar in those with and without a prolonged second stage in first delivery (2.8% versus 2.8%; adjusted odds ratio [aOR] 1.35, 95% CI 0.96–1.90). After adjustment for mode of delivery, prolonged second stage was also not associated with subsequent sPTB in those who delivered by spontaneous and operative vaginal delivery. Those delivered by second‐stage caesarean section in the first delivery had a higher risk of sPTB in the second delivery (25/526, 4.8%; aOR 2.66, 95% CI 1.71–4.12; p < 0.001), with a more pronounced risk in those with second‐stage caesarean following a prolonged second stage of labour (15/259, 5.8%; aOR 3.40, 95% CI 1.94–5.94; p < 0.001). Conclusion: Second‐stage duration in a first term vaginal delivery is not associated with subsequent sPTB. The risk of sPTB is increased following second‐stage caesarean section, particularly if performed after a prolonged second stage. Tweetable abstract: Second‐stage caesarean delivery, particularly after prolonged second stage, increases the risk of preterm birth. Tweetable abstract: Second‐stage caesarean delivery, particularly after prolonged second stage, increases the risk of preterm birth.